Immune mechanisms of depression in rheumatoid arthritis - Brock, James; Basu, Neil; Schlachetzki, Johannes C.M.; Schett, Georg; McInnes, Iain B.; Cavanagh, Jonathan (Nature Reviews Rheumatology, 2023)
Depression is a common and disabling comorbidity in rheumatoid arthritis that not only decreases the likelihood of remission and treatment adherence but also increases the risk of disability and mortality in patients with rheumatoid arthritis. Compelling data that link immune mechanisms to major depressive disorder indicate possible common mechanisms that drive the pathology of the two conditions. Preclinical evidence suggests that pro-inflammatory cytokines, which are prevalent in rheumatoid arthritis, have various effects on monoaminergic neurotransmission, neurotrophic factors and measures of synaptic plasticity. Neuroimaging studies provide insight into the consequences of inflammation on the brain (for example, on neural connectivity), and clinical trial data highlight the beneficial effects of immune modulation on comorbid depression. Major depressive disorder occurs more frequently in patients with rheumatoid arthritis than in the general population, and major depressive disorder also increases the risk of a future diagnosis of rheumatoid arthritis, further highlighting the link between rheumatoid arthritis and major depressive disorder. This Review focuses on interactions between peripheral and central immunobiological mechanisms in the context of both rheumatoid arthritis and major depressive disorder. Understanding these mechanisms will provide a basis for future therapeutic development, not least in depression.
CRIS-Team Scopus Importer:2023-12-08